Pengaruh Likuiditas, Aktivitas Dan Leverage Terhadap Profitabilitas Serta Dampaknya Dalam Memprediksi Kondisi Financial Distress Pada Perusahaan Ritel Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2023 - Hasanudin Hasanudin; Cristine Prestarika Lukito (Journal of Innovative and Creativity, 2026)
The Studi aims to determine the effect of Liquidity Ratio, Activity Ratio, Leverage Ratio To Profitability Ratio and Its Impact In Predicting The Condition Of Financial Distress On Retail Company Listed In Indonesia Stock Exchange. The Financial Distress was measured throught Altman Z’Score, Liquidity Ratio was measured throught Current Ratio (CR), Activity Ratio was measured throught Total Assets Turnover (TATO), Leverage Ratio was measured throught Debt to Equity Ratio (DER) and Profitability ratio was measured throught Net Profit Margin (NPM). The Research was a quantitative study using the financial report of the companies listed on the Indonesia Stock Exchange (BEI). The Sampling tehnique in this study was purpose sampling. The samples used in this study 5 companies, which were listed on the Indonesia Stock Exchange (BEI) in period 2014-2023, in order to obtain the data of 50 companies from the financial Statement are made data panel. The analytical method is descriptive analysis.The data were analyzed through multipel linear regression analysis and processed with software Eviews 13.0. The result showed (1) current ratio with prob. 0.1612 not had and no significant effect on the net profit margin , (2) total assets turnover with prob 0.1490 not had and no significant effect on the net profit margin, (3) debt to equity ratio with prob. 0.1369 not had and no significant effect on the net profit margin (4) current ratio, total assets turnover and debt to equity ratio simultaneously with prob. 0.032619 a had positive significant affected the net profit margin, (5) net profit margin with prob. 0.0216 had a positive significant on the prediction of financial distress.